Supply chain product innovation considering jointly held options under uncertain demand. (May 2023) - Liu, Feng; Tan, Yingshuang; Huang, Xingjun; Sarkar, Sudipto; Zhang, Xueqing
Abstract: Demand uncertainty substantially impacts the optimal decision for supply chain innovation investment despite the recognized importance of new product and technology investment in the supply chain. To this end, an improved real options game model is provided to analyze the influence of various supply chain operating decisions on optimal investment timing and the option value of supply chain firms. According to the findings, market demand volatility and drift rate are favorably connected with the investment threshold, whereas the profit distribution coefficient negatively correlates with the firm investment threshold. Compared with decentralized decision-making, centralized decision-making in the supply chain has the highest investment efficiency and more excellent investment option value. However, choosing it is difficult, particularly when market volatility is high. Surprisingly, the quantity discount contract aid in resolving this issue. Highlights: A real options game model based on a quantity discount contract is presented for the first time. Supply chain companies jointly holding option investments under uncertainty are considered. The entry of the quantity discount contract helps to balance investment risk and improve investment efficiency.